PENGARUH VARIABEL CELAH UDARA TERHADAP FLUKS MAGNET PADA GENERATOR PERMANEN MAGNETIK AXIAL FLUKS - Abubakar, Syafriyudin; suyanto, Muhammad; Pambudi, Prasetyono Eko (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), Universitas AKPRIND Indonesia Yogyakarta, 2024)
Generators that use permanent magnets do not require initial excitation to produce voltage. where the generator design is an axial flux type using a ceramic type permanent magnet (NdFeB), and uses two flanking stator rotors. For electricity use, the AC voltage is changed to DC voltage using a rectifier for charging the accumulator. The air gap in an axialflux generator is the distance between the rotor and stator. The air gap is also a place for the magnetic field to move through the coils in the stator which ultimately produces a magnetic flux value which will influence the amount of induced voltage produced. The faster the rotation produced, the greater the voltage produced, but the frequency value will also increase, so that this generator is only limited to 400 rpm rotation, at a frequency value of 50 Hz, producing an effective voltage of ± 22 V with an air gap distance ( δ) is 2 mm, the frequency measurement has an error of 10-20 Hz and an error percentage of 5-10%, with the results of the induced current measurement having the same voltage